Sade and Lacan – and the seam - Couy, Venus Brasileira (2016)
The essay articulates the painting "The origin of the world" of Courbet with the final scene of The Philosophy in the Bedroom of Sade. The Courbet's screen presents body on scene. Although the sheet makes the body’s frame, there is no strip-tease, from the outset sex discovered is already there, in the foreground. There is no revelation or secret to bare. Joy inscribed, painted, introduces its rupture, its violence. This is his tragic character, loss, absence and death. On screen, the crudeness in the picture scares, lures, nets. There is no veil but horror. However, there is no way to portray the Real. As Lacan proposed the Real is irreducible. There is no significant or picture to represent it. In the seventh chapter of Philosophy in the Bedroom Lady Mistival becomes the victim, which puts an end to the work and education of Eugénie. The student sews the vagina and the anus of her mother. The seam ends the scene. Maybe, just right "sewing the horror", plugging it, as did Eugénie, is possible to glimpse something that escape the Real, as if such a "getaway" was possible. Sewing up the mother’s hole, "shut up" the mother by the hole down, the origin of life.